Embodied Cognition in an OSNK Mathematics Olympiad Winner: Geometry vs. Algebra Problem Solving - Hamdan Yuafie Ni’am; Suwarno (Riemann: Research of Mathematics and Mathematics Education, 2026)
This study aims to describe the characteristics of embodied cognition that emerge when a student who won the National Science Olympiad (OSN) in Mathematics solves OSN-level geometry and algebra problems for the first time. This study uses a qualitative descriptive approach with one subject, namely an 11th-grade student who won the 2025 District OSN. Data were collected through video and audio recordings using two mobile phones, multimodal observation sheets, and reflective interviews. Two types of problems were used as instruments: geometry and algebra. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that the subject's embodied cognition in solving OSN-level mathematics problems was manifested through the integration of gestures and utterances. Writing gestures appeared consistently and dominantly across all stages of problem-solving, both in geometry and algebra questions, as a means of organizing information, planning, and executing solutions. Representational and pointing gestures were limited and used contextually in both geometry and algebra questions to aid visualization and confirm solution steps. In terms of utterances, the subject showed relatively stable patterns through variations in tone of voice, facial expressions, gaze direction, and body posture that supported the thinking process. These findings confirm that mathematical problem-solving involves the simultaneous integration of verbal and nonverbal aspects, with embodied cognition playing an important role in supporting high-level mathematical thinking